ANALISIS TINGKAT KERENTANAN BENCANA: Studi Kasus: Kawasan Cagar Budaya Candi Muara Jambi - Sipayung, Wendy Yudistira; Maryani, Enok; Somantri, Lili; Setiawan, Iwan; Sitepu, Surianto (Majalah Ilmiah METHODA, 2023)
Kawasan Cagar Budaya Candi Muara Jambi is one of the cultural heritage and national heritage in Jambi Province, its location along the Batanghari watershed has a threat to the Batanghari river overflow flood disaster. This study aims to analyze and map the level of disaster vulnerability with the aim of reducing the impact of losses and the impact of the population exposed to disasters.  Determination of the level of disaster vulnerability is done with several vulnerability parameters, namely social, economic, physical and environmental vulnerability. In this study, a Geographic Information System (GIS) approach was used to analyze the level of disaster vulnerability using weighting scoring techniques and overlay techniques. This research used secondary data. Based on the results of the study obtained information that the level of vulnerability of flood disasters in the study area is at a moderate level of vulnerability with a high level of vulnerability parameter, namely economic vulnerability with a moderate level of vulnerability parameter, namely social, physical and environmental vulnerability.